China's New Foreign Policy Military Modernisation, Multilateralism and the 'China Threat' - Pradt, Tilman; SpringerLink (Online service) (Cham : Springer International Publishing (Imprint), 2016)
This book analyses how China overcame its meagre reputation in the early 1990s to become an aggressively growing military power and rising threat to the international system. The author focuses on China's new multilateral foreign policy approach, ambitious military build-up programme and economic cooperation initiatives. This book presents a much-needed comparative perspective of China in terms of foreign policy, seeking to develop analytical tools to assess China's motivations and moves. The author suggests that understanding China's new foreign policy, its tactics in multilateral organisations, and approaches to conflict resolutions are elementary to grasp the new realities of international relations, particularly relevant to newly established institutions in the evolving Asian political system which require basic knowledge for analysing the politics in this continent. This book uses an innovative approach, a qualitative analysis of China's foreign policy addressing criteria of reputation management, to overcome the perceived 'China threat'. Tilman Pradt obtained his PhD in political science at Freie Universität Berlin, Germany. His thesis focused on China's new foreign policy. He is a supervisor and contributing analyst at the geostrategic analysis and business consultancy Wikistrat, and works as a senior advisor for companies and business associations.
1.- Introduction - China's new foreign policy -- 2.- The 'China Threat' -- 3 - China's Military Modernisation Programme -- 4 - Threatening Moves -- 5 - Strategic considerations -- 6 - Assessment 'China threat' -- 7 - China's approach towards ASEAN -- 8 - The SCS territorial disputes -- 9 - Assessment China-ASEAN (Case study Indonesian Workshops) -- 10 - Conclusion - China's new foreign policy .
Keywords: International relations; Asia-Politics and government; Foreign Policy